2006
DOI: 10.2341/05-118
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-delay Curing: Influence of Initial Irradiance and Delay Time on Shrinkage Stress and Microhardness of Restorative Composites

Abstract: ©Operative Dentistry, 2006, 31-5, 610-615 CSC Pfeifer • RR Braga • JL Ferracane Clinical RelevanceNew photoactivation protocols need to be tested before being recommended for clinical use. This study suggests that pulse-delay curing may be an efficient way to reduce polymerization shrinkage stress without compromising degree of conversion or polymer network structure. SUMMARYObjectives: Evaluate the influence of pulse-delay curing on shrinkage stress and microhardness of 2 restorative composites (Herculite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
0
28
0
12
Order By: Relevance
“…The soft-start polymerization technique is characterized by a low initial light intensity followed by high-intensity irradiation. It has been reported that the soft-start polymerization method provided twofold advantages: an increase in resindentin bond strength in box-shaped cavities 16) and reduced polymerization shrinkage stress without compromising the degree of conversion into a polymer network 17) . However, Class I and II composite restorations clinically placed with a soft-start technique showed no significant improvements in terms of postoperative sensitivity to cold or reduction in marginal stress 6) .…”
Section: Discussionmentioning
confidence: 99%
“…The soft-start polymerization technique is characterized by a low initial light intensity followed by high-intensity irradiation. It has been reported that the soft-start polymerization method provided twofold advantages: an increase in resindentin bond strength in box-shaped cavities 16) and reduced polymerization shrinkage stress without compromising the degree of conversion into a polymer network 17) . However, Class I and II composite restorations clinically placed with a soft-start technique showed no significant improvements in terms of postoperative sensitivity to cold or reduction in marginal stress 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these methods have been shown to reduce contraction rate, stress or cusp deflection in cavity preparations when measured in the laboratory, but to different extents. 87,[101][102][103] It is likely that the difference in outcomes is related to the initial irradiance level or ramp-up speed, as well as the delay time when using the "pulse delay" mode, since these will dictate the initial curing rate and may limit any chance for molecular relaxation to reduce stress. 90,103 It is also likely that the time needed to produce curing with sufficient molecular flow may not be clinically practical by most standards.…”
Section: What Can the Clinician Do To Minimize The Effect Of Contractmentioning
confidence: 99%
“…87,[101][102][103] It is likely that the difference in outcomes is related to the initial irradiance level or ramp-up speed, as well as the delay time when using the "pulse delay" mode, since these will dictate the initial curing rate and may limit any chance for molecular relaxation to reduce stress. 90,103 It is also likely that the time needed to produce curing with sufficient molecular flow may not be clinically practical by most standards. One study clinically evaluated the effect of a typical, continuous curing protocol vs a softstart method for Class V composite restorations and saw no difference between the two.…”
Section: What Can the Clinician Do To Minimize The Effect Of Contractmentioning
confidence: 99%
“…복합레진 수복물의 중합수축은 적층법을 통한 충전과 치 아와 복합레진 계면에 저점도 이장재의 사용 6) 등으로 인해 감소시킬 수 있었다. 최근에는 중합수축을 감소시키기 위한 다양한 중합방법이 개발되었으며, 이러한 방법은 재료가 겔 화 또는 유리화 지점 이전 단계에 머무는 시간을 증가시킴 으로써 중합수축을 감소시킬 수 있다 7) . 최근에 소개된 연성 중합방법 (soft-start polymeriza- 18,19) , 이는 표본의 준비과정, 재료의 성질, 접착기질의 이질성 또는 술 식민감성 등에 의해 영향을 받을 수 있다 18) .…”
unclassified